Asset Structure and Business Orientation of Regional Government-Owned Enterprises (BUMD) in Indonesia: Evidence from Correspondence Analysis - Hery Syaerul Homan; Sani Susanto (Universitas Ekuitas Indonesia, 2025)
Introduction/Main Objectives: The research examines how the structure of assets in Regional Government-Owned Enterprises (BUMDs) in Indonesia reflects their orientation in the sector they operate in. Background Problems: The paper addresses the problem of whether asset composition is significantly associated with business sectors and how such distribution patterns reveal the underlying public or commercial orientation of BUMDs in Indonesia. Novelty: This paper offers a novel empirical mapping of asset orientation using Correspondence Analysis, a method rarely applied in public sector financial research. Research Methods: A descriptive quantitative approach was utilized using secondary data from the report by Statistics Indonesia about BUMDs in 2023. The data were analyzed at the sectoral level of BUMD companies, originally expressed as percentage composition of four types of assets. The original percentage data were then converted into a contingency table format to be utilized for Correspondence Analysis and the Chi-square Test to determine the significance of the relation between various sectors and assets. Finding/Results: The study finds a statistically significant relationship between asset types and business sectors, with visual mappings showing that commercial sectors cluster around current assets while public-oriented sectors concentrate on fixed assets. Sectors such as finance, trade, and information emphasize liquidity, whereas construction and health prioritize infrastructure-heavy capital. Conclusion: Asset structures of BUMDs align with sectoral mandates and business orientations. These findings offer insights for regulators and enterprise managers to better align financial planning with institutional mission and to encourage the use of multivariate visual tools in public finance research.